WNT8B as an Independent Prognostic Marker for Nasopharyngeal Carcinoma - Ngernsombat, Chawalit (Curr Oncol, 2021)
Background: Members of the Wnt signaling pathway have been shown to play a role in nasopharyngeal carcinoma (NPC) progression. Aim: The purpose of this study was to investigate WNT8B protein expression in NPC patients using tissue microarray (TMA) analysis and to evaluate its correlation with patient survival and clinical parameters. Methods: A total of 82 NPC cases, together with six normal nasopharyngeal tissue samples, were targeted to construct the TMA blocks. The WNT8B protein expression was evaluated by immunohistochemistry and its correlation to the clinicopathological features was investigated. Results: Sixty-two of 82 (75.6%) cases exhibited high WNT8B protein expression while 20/82 (24.4%) cases appeared to have low WNT8B expression. The univariate analysis revealed that systemic metastasis was associated with patient 5-year survival. The multivariate Cox proportional hazard regression analysis showed that WNT8B expression and systemic metastasis were significantly associated with the survival of NPC patients. Furthermore, there was no correlation found between the WNT8B protein expression and other clinicopathological parameters. Conclusion: Our results suggest that the expression of WNT8B is associated with NPC patients’ survival and could serve as an independent prognostic factor for NPC patients.